Epidemiological study of the outbreak of waterborne and foodborne diseases in Kurdistan province - ابراهیم زاده ebrahimzadeh (Mashhad University of Medical Sciences, 2019)
Background and Aim: Nowadays, because of several reasons, the incidence of waterborne and foodborne diseases is increasing in the world. Hence, this study was conducted to analyze the data on the prevalence of waterborne and foodborne diseases in Kurdistan province. Materials and Methods: This study was a descriptive analytical study that analyzed the outbreaks reported in Kurdistan province from 2011 to 2017. In this study, Chi-square test was applied to assess the relationships between the sources of the outbreaks (water or food) and the studied variables, including age, sex, cause of disease, region, place of outbreak, time of outbreak, status of drinking water distribution network, and status of chlorination. STSTA software Version 13 was used to perform the statistical analysis. Results: According to the results of this study, of a total of 390 outbreaks reported during the studied period, 90 cases (23.08%) were caused by water, 261 cases (66.92%) were caused by food, and 39 cases (10%) had an unknown source. Concerning the location, of all cases of waterborne outbreaks, 69 cases of outbreaks (76.67%) occurred in rural areas and 21 cases of outbreaks (23.33%) occurred in urban areas. On the other hand, of all cases of foodborne outbreaks, 147 cases of outbreaks (56.32%) occurred in urban areas and 114 cases of outbreaks (43.68%) occurred in rural areas and there was a significant relationship between the outbreak and the location of residence in the city or village (P-value <0.001). Conclusion: Based on the results of this research, observing food hygiene during the preparation and cooking of food and supervising the supply of healthy drinking water have a significant role in reducing the prevalence of waterborne and foodborne outbreaks.